EFFORTS TO IMPROVE ISLAMIC CHARACTER EDUCATION THROUGH INDIVIDUAL COUNSELING WITH A REALITY APPROACH FOR SEVENTH-GRADE STUDENTS AT SLB PUTRA MANDIRI LAMONGAN - Sugeng Tri Susila; Saefrudin Saefrudin; Anwar Sholikhin (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study is entitled “Efforts to Improve Islamic Character Education through Individual Counseling with a Reality Approach for Seventh-Grade Students at SLB Putra Mandiri Lamongan.” The purpose of this study is to improve students’ Islamic character education, particularly in obeying school rules, through individual counseling using a reality approach for seventh-grade students at SLB Putra Mandiri Lamongan. The research method used in this study is Action Research, which consists of two cycles. Each cycle includes the following stages: planning, implementation, observation, and reflection. Based on the results of the action research, it can be concluded that individual counseling with a reality approach is effective in improving Islamic character education among seventh-grade students at SLB Putra Mandiri Lamongan. Furthermore, the researcher recommends: (1) Teachers who experience similar difficulties are encouraged to apply individual counseling with a reality approach to improve students’ Islamic character education. (2) To achieve optimal results, teachers are expected to design individual counseling with a reality approach that is more engaging and varied.